Human Cytomegalovirus Upregulates Expression of the Lectin Galectin 9 via Induction of Beta Interferon - McSharry, Brian P. (American Society for Microbiology, 2014)
Regulation of the lectin galectin 9 (Gal-9) was investigated for the first time during human cytomegalovirus (HCMV) infection. Gal-9 transcription was significantly upregulated in transplant recipients with reactivated HCMV in vivo. In vitro, Gal-9 was potently upregulated by HCMV independently of viral gene expression, with interferon beta (IFN-β) identified as the mediator of this effect. This study defines an immunoregulatory protein potently increased by HCMV infection and a novel mechanism to control Gal-9 through IFN-β induction.